Association Between Kidney Function Decline and Baseline TNFR Levels or Change Ratio in TNFR by Febuxostat Chiefly in Non-diabetic CKD Patients With Asymptomatic Hyperuricemia - Gohda, Tomohito; Yanagisawa, Naotake; Murakoshi, Maki; Ueda, Seiji; Nishizaki, Yuji; Nojiri, Shuko; Ohashi, Yasuo; Ohno, Iwao; Shibagaki, Yugo; Imai, Naohiko; Iimuro, Satoshi; Kuwabara, Masanari; et al. (Frontiers in Medicine, 2021)
Background: The levels of circulating tumor necrosis factor receptor (TNFR) 1 and 2 help predict the future decline of estimated glomerular filtration rate (eGFR) chiefly in patients with diabetes. It has been recently reported that the change ratio in TNFR1 by SGLT2 inhibitor treatment is also related with future GFR decline in patients with diabetes. The aims of this study are to investigate the association between baseline TNFR levels and early change in TNFR levels by the non-purine selective xanthine oxidase inhibitor, febuxostat, and future eGFR decline chiefly in chronic kidney disease (CKD) patients without diabetes. Methods: We conducted a post-hoc analysis of the FEATHER study on patients with asymptomatic hyperuricemia and CKD stage 3, who were randomly assigned febuxostat 40 mg/day or matched placebo. This analysis included 426 patients in whom baseline stored samples were available. Serum TNFR levels at baseline were measured using enzyme-linked immunosorbent assay. Those levels were also measured using 12-week stored samples from 197 randomly selected patients. Results: Compared with placebo, short-term febuxostat treatment significantly decreased the median percent change from baseline in serum uric acid (−45.05, 95% CI −48.90 to −41.24 mg/dL), TNFR1 (1.10, 95% CI−2.25 to 4.40), and TNFR2 (1.66, 95% CI −1.72 to 4.93), but not TNFR levels. Over a median follow-up of 105 weeks, 30 patients (7.0%) experienced 30% eGFR decline from baseline. In the Cox multivariate model, high levels of baseline TNFR predicted a 30% eGFR decline, even after adjusting for age, sex, systolic blood pressure, high sensitivity C-reactive protein, uric acid, and presence or absence of febuxostat treatment and diabetes, in addition to baseline albumin to creatinine ratio and eGFR. Conclusion: Early change in circulating TNFR levels failed to predict future eGFR decline; however, regardless of febuxostat treatment, the elevated baseline level of TNFR was a strong predictor of 30% eGFR decline even in chiefly non-diabetic CKD patients with asymptomatic hyperuricemia.